Human impact on symbioses between aquatic organisms and microbes - Stock, Willem (2021)
Aquatic organisms rely on microbial symbionts for coping with various challenges they encounter during stress and for defending themselves against predators, pathogens and parasites. Microbial symbionts are also often indispensable for the host's development or life cycle completion. Many aquatic ecosystems are currently under pressure due to diverse human activities that have a profound impact on ecosystem functioning. These human activities are also expected to alter interactions between aquatic hosts and their associated microbes. This can directly impact the host's health and - given the importance and widespread occurrence of microbial symbiosis in aquatic systems - the ecosystem at large. In this review, we provide an overview of the importance of microbial symbionts for aquatic organisms, and we consider how the beneficial services provided by microbial symbionts can be affected by human activities. The scarcity of available studies that assess the functional consequences of human impacts on aquatic microbial symbioses shows that our knowledge on this topic is currently limited, making it difficult to draw general conclusions and predict future changes in microbial symbiont-host relationships in a changing world. To address this important knowledge gap, we provide an overview of approaches that can be used to assess the impact of human disturbances on the functioning of aquatic microbial symbioses.